Correlational Study Between the Improvement of Reading Achievement and Student’ Speaking Skill at The First Grade of SMAN 1 Rawamerta Karawang - Neneng Rahayu Aprilia; Melly Lesvia Lukita (IKIP Siliwangi, 2019)
The objectives of this research entitled correlational study between the improvement of reading achievement and their students speaking skill are to investigate the students reading achievement and to analyze the correlation between students reading score and their speaking ability. The method used in this research is correlational method. The population of this research was SMAN 1 Rawamerta Karawang and the sample of this research was the first grade students of SMAN 1 Rawamerta Karawang. The results of this research showed that speaking coefficient regression is Y=4.028 + 0.898X. The conclusion of this research there is high correlation between reading and speaking equal to 0.978 (perfect correlation).